The Small World of Adult Hippocampal Neurogenesis - Overall, Rupert W.; Kempermann, Gerd (Frontiers in Neuroscience, 2018)
Making mechanistic sense of genetically complex biological systems such as adult hippocampal neurogenesis poses conceptual and many practical challenges. Transcriptomics studies have helped to move beyond single-gene approaches and have greatly enhanced the accessibility to effects of greater numbers of genes. Typically, however, the number of experimental conditions compared is small and the conclusions remain correspondingly limited. In contrast, studying complex traits in genetic reference populations, in which genetic influences are varied systematically, provides insight into the architecture of relationships between phenotypes and putative molecular mechanisms. We describe that the correlation network among transcripts that builds around the adult neurogenesis phenotype and its endophenotypes is, as expected, a small-world network and scale free. The high degree of connectivity implies that adult neurogenesis is essentially an ‘omnigenic’ process. From any gene of interest, a link to adult hippocampal neurogenesis can be constructed in just a few steps. We show that, at a minimum correlation of 0.6, the hippocampal transcriptome network associated with adult neurogenesis exhibits only 2 ‘degrees of separation’. This fact has many interesting consequences for our attempts to unravel the (molecular) causality structure underlying adult neurogenesis and other complex biological systems. Our article is not written with the expert on network theory in mind but rather aims to raise interest among neurobiologists, active in neurogenesis and related fields, in network theory and analysis as a set of tools that hold great promise for coping with the study of ‘omnigenic’ phenotypes and systems.